(untitled) (Bioagro, 2020)
In Latin America and the Caribbean, rice hybrids had become into an important technological alternative to achieve productivity risings on this crop, improving efficiency in the use of inputs (land, water, fertilizer), and contributing to satisfy the increasing food needs on a sustainable way. Beside yield risings, development and adoption of rice hybrid in Venezuela could encourage the use of high quality certified seed, boosting seed market and reducing diseases and other pests. On this focus, in 2010 the crosses for rice hybrids development were started, with the aim of obtain adapted high yielding hybrid cultivars with grain quality adapted to the Venezuelan mills requirements. Using a breeding method based upon cytoplasmatic male sterility or three-line system, RHA-180 was identified. The hybrid RHA-180 showed good agronomic performance and good grain quality, with grain yield 27.06 % higher, on average, than SD20A variety. All of this reflects the good adaptation of RHA-180 to Venezuelans rice crop conditions, and its suitability as the first Venezuelan rice hybrid.